2015
DOI: 10.1155/2016/3643824
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti‐inflammatory, and Antiulcer Potential of Manuka Honey against Gastric Ulcer in Rats

Abstract: Gastric ulcers are among the most common diseases affecting humans. This study aimed at investigating the gastroprotective effects of manuka honey against ethanol-induced gastric ulcers in rats. The mechanism by which honey exerts its antiulcer potential was elucidated. Four groups of rats were used: control, ethanol (ulcer), omeprazole, and manuka honey. Stomachs were examined macroscopically for hemorrhagic lesions in the glandular mucosa, histopathological changes, and glycoprotein detection. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 45 publications
8
102
0
1
Order By: Relevance
“…However, their duration of in-tervention was very shorter than what used in our study. A study reported that manuka honey keeps GSH in the reduced form and protects its activity; it also protects GPx and SOD activity and removes lipid hydroperoxides and hydrogen peroxide from the gastric mucosal cell of rats (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, their duration of in-tervention was very shorter than what used in our study. A study reported that manuka honey keeps GSH in the reduced form and protects its activity; it also protects GPx and SOD activity and removes lipid hydroperoxides and hydrogen peroxide from the gastric mucosal cell of rats (45).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of honey was long established through various studies [14, 16, 23, 29] on non-arid region honey, yet nothing was available on arid region varieties. The research results demonstrated here indicate that arid region honey also possesses anti-inflammatory effects similar to previously studied non-arid honey types.…”
Section: Discussionmentioning
confidence: 99%
“…Habib et al [21] compared non arid region honey varieties such as Black Forest and Manuka to arid region honey by using biochemical assays. Non-arid region varieties of honey such as Manuka [23], Gelam [16] and Tualang [24] have been extensively studied in regards to their antioxidant, anti-inflammatory and anti-tumor properties. Results from these studies were promising.…”
Section: Introductionmentioning
confidence: 99%
“…It could have preferred to achieve the truest result with more animal groups, but the rule of Three Rs (Replacement, Reduction, and Refinement) emphasized in The Principles of Humane Experimental Techniques was the genuine indicator in this study (Kirk, ). Therefore, inspired by literature, only two different concentrations of each honey sample were used for the applying of animal experiments (Almasaudi et al, ; Fazalda, Quraisiah, & Nur Azlina, ; Nasuti, Gabbianelli, Falcioni, & Cantalamessa, ). It was well‐known that the goal of reduction was to reduce the numbers of animals used to obtain information about a given amount and precision.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the second estimation which was emphasized as non‐relationship between using honey samples and measured serum parameters during the experimental period could be supported by a clinical report. This report relating to the affection of manuka honey on triglycerides, total cholesterol, HDL‐cholesterol, and LDL‐cholesterol claimed that there was no significant effect between lipid profiles and urease disease (Almasaudi et al, ). Except for the minor differences of serum lipid levels in our experimental model, thankfully it was found that none of the selected concentrations of honeys showed hepatotoxic effects seen in the presence of hepatocellular degeneration and necrotic changes.…”
Section: Discussionmentioning
confidence: 99%